CXC Chemokines as Therapeutic Targets and Prognostic Biomarkers in Skin Cutaneous Melanoma Microenvironment - Zhou, Xuezhi; Peng, Manjuan; He, Ye; Peng, Jingjie; Zhang, Xuan; Wang, Chao; Xia, Xiaobo; Song, Weitao (Frontiers in Oncology, 2021)
Background: Skin Cutaneous Melanoma (SKCM) is a tumor of epidermal melanocytes induced by gene activation or mutation. It is the result of the interaction between genetic, constitutional, and environmental factors. SKCM is highly aggressive and is the most threatening type of skin tumor. The incidence of the disease is increasing year by year in the world, and it is the main cause of death in skin tumors. CXC chemokines in the tumor microenvironment can regulate the transport of immune cells and the activity of tumor cells, thus playing an anti-tumor immunological role and affecting the prognosis of patients. However, the expression level of CXC chemokine in SKCM and its effect on prognosis are still unclear. Method: Oncomine, UALCAN, GEPIA, STRING, GeneMANIA, cBioPortal, TIMER, TRRUST, DAVID 6.8, and Metascape were utilized in this research. Result: The transcription levels of CXCL1, CXCL5, CXCL8, CXCL9, CXCL10, and CXCL13 in SKCM tissues were significantly higher than those in normal tissues. The pathological stage of SKCM patients is closely related to the expression levels of CXCL4, CXCL9, CXCL10, CXCL11, CXCL12 and CXCL13. SKCM patients with low transcription levels of CXCL4, CXCL9, CXCL10, CXCL11, and CXCL13 have a significantly better prognosis. The differential expression of CXC chemokines is mainly related to inflammatory response, immune response and cytokine mediated signaling pathways. Our data indicate that the key transcription factors of CXC chemokines are RELA, NF-κB1 and SP1. The targets of CXC chemokines are mainly the SRC family of tyrosine kinases (LCK, LYN, SYK), mitogen-activated protein kinases (MAPK2, MAPK12, and MAPK14), and ART. We found a significant correlation between CXC chemokine expression and immune cell infiltration in SKCM. Conclusions: Our results provided a framework for developing new pathological molecular networks related to SKCM.